Perception and Clinical Assessment of Fetal Movement in Nursing Practice: Implications for Maternal–Fetal Surveillance and Perinatal Outcomes - Almarzooq, Radiyh Abdullah; Nuha Fahad Mutlaq Almutlaq,; Entesar Mohammed M Alsaadi,; Hajar Lafi Alian Almutiri,; Doaa Salim Hamid Alabsi,; Hadeel Saleh Aljohani,; Ghandar ahamidaimawlid,; Samahzid Alshuraymi ,; Layla Hussein Eissa Al Habbabi,; Salma Mohammed Ali Almohanna,; Bayan Ebraheem Ali Alkhalifah,; Hayat Saleh Alkhlaifi, (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Fetal movement is a critical indicator of fetal wellbeing and neurological integrity. Its perception by pregnant individuals serves as an accessible, patient-centered marker for maternal–fetal surveillance. Nursing practice emphasizes awareness and structured monitoring, such as kick counts, to detect deviations that may signal hypoxemia or placental insufficiency. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> To explore the clinical significance of fetal movement perception, its role in nursing care, and implications for maternal–fetal outcomes. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review synthesizes current evidence and guidelines on fetal movement monitoring, including physiologic basis, timing of quickening, influencing factors, and structured assessment strategies. It also examines nursing interventions and interprofessional approaches for managing decreased fetal movement. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Maternal perception of fetal movement reflects neuromuscular maturation and offers early warning of potential compromise. Structured monitoring, such as count-to-10 kick counts, enhances detection of abnormal patterns. Reports of decreased movement correlate with increased risk of adverse outcomes, including stillbirth. Prompt evaluation using nonstress tests (NST) and biophysical profiles (BPP) is essential. Nursing roles encompass triage, patient education, and coordination of care, ensuring timely escalation and reducing delays in intervention. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Fetal movement monitoring remains a low-cost, effective strategy for early identification of fetal compromise. Nursing professionals play a pivotal role in education, surveillance, and interprofessional coordination, optimizing perinatal outcomes through timely response and patient-centered care.